Feasibility of extraction methods of essential oil from pineapple peels - Mohamad, Nurshazana (2018)
The pineapple industry produces substantial amount of solid wastes where the value of waste generated was reported as high as 75-80%. Peels, cores, stems, crowns and pulp were removed and becoming waste during the processing. Since disposal of these wastes is expensive due to high transportation cost and a limited availability of landfills, they are mostly being unscrupulously dumped and openly burnt. The current practice of dumping the pineapple wastes can cause microbial spoilage and environmental problems due to high contents of moisture and sugar. Pineapple wastes including peel composed of aromatic compound such as esters, alcohols, acids, aldehydes and ketones, in which it can be extracted as essential oil. The essential oil plays an importance use in industrial applications such as in aromatherapy, fragrances and flavors in food and beverages as well as personal care. However, up to date, there are very limited studies on the extraction methods of essential oil from pineapple wastes. Considering the value of pineapple peel as a feedstock for essential oil extraction, the present study was conducted to identify a feasible method for the extraction of essential oil from pineapple peel. Three methods have been carried out in this study; (1) hydro-distillation (HD), (2) hydro- distillation with enzyme-assisted (HDEA), and (3) supercritical fluid extraction (SFE). Among the methods used, only SFE resulted in the formation of essential oil with 0.17% (w/w) yield, whereas HD and HDEA methods only produced the hydrosol with the yield of 70.65% and 80.65%, respectively. The microscopic observation using scanning electron microscope (SEM) of the sample’s cell wall substantiated that only SFE method showed the rupture of the essential oil gland after the extraction process. The gas chromatography-mass spectrometry (GC-MS) analysis showed that the major volatile compounds identified in the essential oil produced through SFE method were propanoic acid ethyl ester (40.25%), lactic acid ethyl ester (19.35%), 2-heptanol (15.02%), propanal (8.18%), 3-hexanone (2.60%) and butanoic acid ethyl ester (1.58%). These important volatile compounds indicate the potential of pineapple peel to be used as a substrate for essential oil production. This study suggested that the SFE is a feasible method for the extraction of essential oil from pineapple peel which produced the major important volatile compounds.